Lobachevskii Journal of Mathematics
http://ljm.ksu.ru
Vol. 14, 2004, 25–32
© A. I. Fedotov
A. I. Fedotov
LEBESGUE CONSTANT ESTIMATION IN
MULTIDIMENSIONAL SOBOLEV SPACE
(submitted by F. Avkhadiev)
ABSTRACT. The norm estimation of the Lagrange interpolation operator is
obtained. It is shown that the rate of convergence of the interpolative
polynomials depends on the choice of the sequence of multiindices and, for
some sequences, is equal to the rate of the best approximation of the
interpolated function.
________________
2000 Mathematical Subject Classification. 65D05.
Key words and phrases. Lagrange interpolation operator, Sobolev space.
|
Introduction
In the paper [1] the collocation method for singular integral equations and
periodic pseudodifferential equations in 1-dimensional Sobolev space was
justified. The crucial role in the justification and error estimation plays the
fact (Lemma 4) that the Lagrange interpolation operator in this space is
bounded. To generalize this results for the multidimensional case the
norm estimation (i.e. estimation of the Lebesgue constant) of the
Lagrange interpolation operator in multidimensional Sobolev spaces is
needed.
Here, we show that in
m-dimensional
Sobolev space Hs(s > m∕2)
the norm of n-order
(n = (n1,n2,...,nm))
Lagrange interpolation operator depends of the function
M(n,s)
which, w.r.t. the choice of the sequence of multiindices
(n),
n →∞, is
either bounded, or grows infinitely.
1. Formulation of the problem
Let’s fix the natural m ∈ N
and denote by N = Nm,
N0 = N0m,
Z = Zm,
R = Rm,
Δ = Δm Cartesian degrees of
the sets of natural N,
natural with zero added N0,
integer Z, real
R numbers and
the interval Δ = (−π; π] ⊂ R
correspondingly. For the elements of these sets
( m-components
vectors) besides the usual operations of addition, subtraction and
multiplication to the number we’ll define the following operations
l⋅k = ∑
j=1ml
jkj,l2 = ∑
j=1ml
j2,l∗k = (l
1k1,l2k2,...,lmkm),[l] = ∏
j=1ml
j,
and the partial order
l < k ≡ &j=1m(l
j < kj),l = (l1,l2,...,lm),k = (k1,k2,...,km).
By n →∞ we’ll
mean, that n
takes the values of sone sequence
(nj),nj ∈ N,nj < nj+1,j = 1, 2,....
Furthermore, in a sake of simplicity we’ll write
min(n)instead of min 1≤j≤m{nj ∣ n = (n1,n2,...,nm) ∈ N}
and
max(n)instead of max 1≤j≤m{nj ∣ n = (n1,n2,...,nm) ∈ N}.
For the fixed s ∈ R
let Hs denote
m-dimensional Sobolev space, i.e.
the closure of all m-dimensional
smooth 2π-periodic
by every variable complex-valued functions w.r.t. the norm
∣∣u∣∣s = ∣∣u∣∣Hs = (∑
l∈Z(1 + l2)s ∣û(l) ∣2)1∕2,
where
û(l) = (2π)−m ∫
Δu(τ)ēl(τ)dτ,l ∈ Z,
are the complex-valued Fourier coefficients of the function
u ∈ Hs w.r.t
the trigonometric monomials
el(τ) = exp(il ⋅τ),l ∈ Z,τ ∈ Δ,i = −1.
It is known that, being equipped with the inner product
< u,v > s = ∑
l∈Z(1 + l2)sû(l)v̂̄(l),u,v ∈ Hs,
Hs
becomes Hilbert space. For the following we’ll assume that
s > m∕2, providing (see e.g.
[2]) the embedding of Hs
in the space of continuous functions.
Let’s fix n = (n1,n2,...,nm) ∈ N,
denote by
In = In1 ×In2 ×⋅⋅⋅×Inm,Inj = {kj ∣ kj ∈ Z, ∣ kj ∣≤ nj},j = 1, 2,...,m,
the set of indices and define uniform partition
Δn = {tk = (tk1,tk2,...,tkm) ∣ k = (k1,k2,...,km) ∈ In,
tkj = kjhj,hj = 2π∕(2nj + 1),j = 1, 2,...,m},
on Δ.
By Pn
we denote Lagrange interpolation operator that assigns to every function
u ∈ Hs
polynomial
(Pnu)(τ) = ∑
k∈Inu(tk)ξn(τ,tk),τ = (τ1,τ2,...,τm) ∈ Δ,
where tk = (tk1,tk2,...,tkm) ∈ Δn,
coinciding with u
in the nodes Δn.
Here
ξn(τ,tk) = ∏
j=1m sin((2nj + 1)(τj − tkj)∕2)
(2nj + 1) sin((τj − tkj)∕2) = [2n+1]−1 ∑
l∈Inel(τ−tk),
1 = (1, 1,..., 1) ∈ N,τ ∈ Δ,tk ∈ Δn,
are fundamental polynomials satisfying
ξn(tl,tk) = 1,l = k,
0,l ⁄= k,l,k ∈ In.
We have to estimate the norm of the operator
P n : Hs → Hs.
2. Preliminaries
The results of this section are technical ones. They are gathered in 2
lemmas to exclude less important details from the proof of the main
result.
Lemma 1. For every
m ∈ N,s ∈ R,s > m∕2
and
n ∈ N
∑
j∈Z((n + j ∗ (2n + 1))2)−s ≤ 2m ∑
l∈N((n ∗ (2l − 1))2)−s.
Proof. To change the set of sum indices from
Z to
N let’s represent
Z as a merge
of two sets: {−l ∣ l ∈ N}
and {l − 1 ∣ l ∈ N}. For
the k-th,
1 ≤ k ≤ m, component
of the vector n + j ∗ (2n + 1)
we’ll obtain
(nk + jk(2nk + 1))2 = (l
k(2nk + 1) − nk)2
= (nk(2lk + lk
nk − 1))2 ≥ (n
k(2lk − 1))2,
jk ∈ Z,jk < 0,lk = −jk ∈ N;
(nk + jk(2nk + 1))2 = (n
k + (lk − 1)(2nk + 1))2 = (n
k + 2nklk + lk − 2nk − 1)2)
= (nk(2lk + lk
nk − 1) − 1)2 ≥ (n
k(2lk − 1))2,
jk ∈ Z,jk ≥ 0,lk = jk + 1 ∈ N.
As to each summand of index l ∈ N
correspond 2m summands
when adding by Z
then
∑
j∈Z((n + j ∗ (2n + 1))2)−s ≤ 2m ∑
l∈N((n ∗ (2l − 1))2)−s.□
Let
Apm = {k ∣ k = (k
1,k2,...,km) ∈ N0,∑
j=1mk
j = p}
be the set of vectors from N0
which component’s sum is p ∈ N0.
By R(Apm) we denote the
number of elements of Apm.
Lemma 2. For every
p, m ∈ N
R(Apm) ≤ mpm−1.
Proof. We’ll show first that
R(Apm) = C
m+p−1p = (m + p − 1)!
p!(m − 1)! ,p ∈ N0,m ∈ N,
| (1) |
and then that
Cm+p−1p ≤ mpm−1,p,m ∈ N.
| (2) |
Let m = 1, then for
every p ∈ N0 the set
Ap 1 contains only one vector,
and hence R(Ap1) = C
pp = p0 = 1. Assume that (1)
is valid for some m ∈ N, and prove
that it is valid then for m + 1.
We’ll construct the set Apm+1 as a
merge of the sets Ajm,j = 0, 1,...,p, adding to
each element of the set Ajmm + 1-th
component equal to p − j,j = 0, 1,...,p.
Then
R(Apm+1) = ∑
j=0pR(A
jm) = ∑
j=0pC
m+j−1j = (m + p)!
m!p! = Cm+1p,
and hence (1) is valid for all p ∈ N0
and m ∈ N.
Now assume that estimation (2) is valid for some
m ∈ N, and prove that it
is valid then for m + 1.
Indeed,
Cm+pp = (m + p)!
m!p!
= Cm+p−1pm + p
m ≤ mpm−1m + p
m = pm(m
p + 1) ≤ (m + 1)pm.□(3)
3. Main results
Theorem 1. For every
s ∈ R,m ∈ N,s > m∕2
and
n ∈ N
following estimation is valid
∣∣Pn∣∣Hs→Hs ≤ 2m−s
2 ms+1
2 M(n,s)1 + ζ(2s − m + 1),
where
M(n,s) = n2
min(n) s,
and ζ(t) = ∑
j=1∞j−t
- is Riemann’s ζ-function
bounded and decreasing for t > 1.
Proof. Let’s fix m ∈ N,s ∈ R,s > m∕2,n ∈ N, choose
an arbitrary function u ∈ Hs
and write Lagrange interpolative polynomial w.r.t. the nodes
Δn for
it
(Pnu)(τ) = ∑
k∈Inu(tk)ξn(τ,tk).
It’s Fourier coefficients are
(Pnû)(l) = [2n + 1]−1 ∑
k∈Inu(tk)ēl(tk),l ∈ In,
0, l ⁄∈ In.
Substituting the values of function u
in the nodes Δn
by its Fourier series expansion we’ll obtain
(Pnû)(l) = [2n + 1]−1 ∑
k∈In(∑
j∈Zû(j)ej(tk))ēl(tk) =
= [2n + 1]−1 ∑
j∈Zû(j) ∑
k∈Inej(tk)ēl(tk) = ∑
j∈Zû(l + j ∗ (2n + 1)).
Further, according to the proof of Lemma 2 [1], we get
∣∣Pnu∣∣s2 = ∑
l∈In(1+l2)s ∣ (P
nû)(l) ∣2 = ∑
l∈In(1+l2)s ∣∑
j∈Zû(l+j∗(2n+1)) ∣2
= ∑
l∈In ∣∑
j∈Z(1 + l2)s
2 û(l + j ∗ (2n + 1)) ∣2
= ∑
l∈In ∣∑
j∈Z(1+l2)s
2 (1+(l+j∗(2n+1))2)−s
2 û(l+j∗(2n+1))(1+(l+j∗(2n+1))2)s
2 ∣2
≤∑
l∈In(∑
j∈Z((1 + l2)∕(1 + (l + j ∗ (2n + 1))2))s
∑
j∈Z ∣û(l + j ∗ (2n + 1)) ∣2(1 + (l + j ∗ (2n + 1))2)s) ≤
≤ max l∈In(∑
j∈Z((1 + l2)∕(1 + (l + j ∗ (2n + 1))2))s)∣∣u∣∣
s2.
It is easy to check that sum
∑
j∈Z((1 + l2)∕(1 + (l + j ∗ (2n + 1))2))s
reaches maximum when l = n,
so using Lemma 1 we have
maxl∈In(∑
j∈Z((1 + l2)∕(1 + (l + j ∗ (2n + 1))2))s)
= ∑
j∈Z((1 + n2)∕(1 + (n + j ∗ (2n + 1))2))s
≤ 2s(n2)s ∑
j∈Z((n + j ∗ (2n + 1))2)−s ≤ 2s+m(n2)s ∑
j∈Z((n ∗ (2j − 1))2)−s
≤ 2s+mM2(n,s) ∑
j∈N((2j − 1)2)−s.
Summands could be estimated as
((2j − 1)2)−s = (∑
k=1m(2j
k − 1)2)−s ≤ m
(∑
k=1m(2jk − 1))2 s,
and using Lemma 2 we obtain
2s+mM2(n,s) ∑
j∈N((2j − 1)2)−s
≤ 2s+mmsM2(n,s) ∑
j∈N(∑
k=1m(2j
k − 1))−2s
= 2s+mmsM2(n,s) ∑
j∈N(2 ∑
k=1mj
k − m)−2s = 2s+mmsM2(n,s) ∑
j∈N0 R(Ajm)
(m + 2j)2s
≤ 2s+mmsM2(n,s) m−2s + ∑
j∈n mjm−1
(m + 2j)2s
≤ 2m−sms+1M2(n,s)(1 + ∑
j∈Nj−(2s−m+1)).
Theorem is proved. □
Denote polynomial of the best approximation to
u ∈ Hs of degree not
higher than n ∈ N0
and the corresponding best approximation
(Snu)(τ) = ∑
l∈Inû(l)e(iτ ⋅ l),En(u)s = ∣∣u − Snu∣∣s,
where (Snu)(τ) is the
n-th partial sum of
Fourier series of u.
Corollary 1. For every s ∈ R,m ∈ N,s > m∕2,n ∈ N
and arbitrary function u ∈ Hs
∣∣u − Pn∣∣s ≤ (1 + 2m−s
2 ms+1
2 M(n,s)1 + ζ(2s − m + 1))En(u)s.
| (4) |
The proof is obvious. □
Corollary 2. For every s ∈ R,m ∈ N,s > m∕2,n ∈ N,
arbitrary function u ∈ Hs
and sequence of indices (nj)j∈N
satisfying
lim n→∞M(n,s) < ∞,
sequence of polynomials
(P nu)
converges to function
u
with the error estimate
∣∣u − Pnu∣∣s = O(En(u)s).
Proof follows directly from Corollary 1.
□
Corollary 3. For any
p, s ∈ R,m ∈ N,p ≥ s > m∕2,n ∈ N
and arbitrary function
u ∈ Hp
the following estimation is valid
En(u)s ≤ (1 + n2)s−p
2 En(u)p.
Proof follows from properties of the best approximation and definitions of norms
in Hs
and Hp.
□
Corollary 3 allows to generalize Corollary 2.
Corollary 4. For any p,s ∈ R,m ∈ N,p ≥ s > m∕2,n ∈ N,
arbitrary function u ∈ Hp
and sequence of indices (nj)j∈N
satisfying
lim n→∞M(n,s)(n2)s−p
2 < ∞,
sequence of polynomials
(P nu)
converges to function
u
with error estimate
∣∣u − Pnu∣∣s = O(En(u)p).
Proof follows from Corollaries 1 - 3.
Remark 1. For any constant C,C ≥ms,
the set {n ∣ M(n,s) ≤ C}
is a cone in N.
Choosing indices from this cone we’ll obtain sequence of interpolation
polynomials converging with estimation (4) where M(n,s)
is substituted by C.
The minimal possible value of M(n,s) = ms
will be on the set
{n ∣ n ∈ N,n = (n1,n2,...,nm),nk = nl, 1 ≤ k,l ≤ m}
of indices with equal components.
References
[1] Fedotov A.I. On the asymptotic convergence of the polynomial collocation
method for singular integral equations and periodic pseudodifferential
equations// Archivum mathematicum. 2002. V.1. P.1-13.
[2] Taylor, M.E. Pseudodifferential operators, Princeton University Press, Princeton
1981.
RESEARCH INSTITUTE OF MATHEMATICS AND MECHANICS, KAZAN STATE
UNIVERSITY, UNIVERSITETSKAYA STR. 17, KAZAN:420008, RUSSIA
E-mail address: fedotov@mi.ru
Received December 5, 2003